Planning Teaching Strategies and Cognitive Processes in a Group of Primary School Teachers - Moreno, Manuel Fernando (2019)
The objective of this article is to identify cognitive processes used in lesson planning among a group of 7 primary school teachers in Bogotá, Colombia, based on semi-structured interviews and content analysis. Lesson planning can be understood as a process allowing cognitive representation of teaching and reflection for developing one´s own pedagogical approach. According to our results, cognitive processes used in planning teaching strategies serve as a representational reference for the teacher which influences pedagogical development among students. It is acknowledged that teacher planning, to a large extent, is a representational process with an underlying cognitive and pedagogical design, subject to each teacher´s own context and experience. These are elements that, in turn, can be recognized and fostered by the institution to promote innovative perspectives within pedagogical practice.